PENGARUH JENIS PAKAN USUS AYAM DAN AMPAS TAHU TERHADAP PERTUMBUHAN LELE DUMBO (Clarias gariepinus) - Irham Falahudin; Syarifah Syarifah; Meysi Rahmalia (Biota, 2016)
Fish as a source of animal protein has several advantages over other animal protein sources, one source of animal protein that is Dumbo catfish. Dumbo catfish fish including fish which is most easily accepted by society. This study aimed to determine the effect of feeding on African catfish (Clarias gariepinus) using chicken intestine and tofu on the growth of catfish. This study was conducted on August 24, 2015 until 24 September 2015. The parameters observed in this study were weight and length. The study was conducted using a randomized block design (RAK) with 4 treatments and 4 groups: feeding by comparing the administration of fish feed manufactured in the form of pellets 100% (control), feed chicken intestines 100%, the feed pulp out of 100%, and chicken intestine feed pulp 50% + 50% Fish test with a weight of 20 grams and 12 cm. With other factors such as pH and temperature equated water. Feeding 2 times a day for 30 days of maintenance. The results showed that there was significant difference between the treatment given to the growth of the weight and length of catfish, feed A1 (chicken intestine 100%) gave the best growth of the African catfish and significantly different from other treatments (P <0.05). Absolute growth of 39.1 grams with a length of 31,2 cm